Mahasiswa Kuliah Kerja Nyata (KKN) Unsuri Melakukan Kegiatan Khotmil Qur’an 30 Juz sebagai Program Kerja - Sabila Aisyah Jamil; Rohmadhotin Fitri; Didit Darmawan; Roidatus Shofiyah; Masfufah Masfufah; Febriarsita Eka Sasmita; She Fira Azka Arifin (Bumi: Jurnal Hasil Kegiatan Sosialisasi Pengabdian kepada Masyarakat, 2024)
The majority of Indonesian citizens are Muslim. The holy book of Islam is the Koran. The focus of dedication in this work program is to carry out Khotmil Qur'an 30 Juz activities. This service uses the Participatory Action Research method where the writer is actively involved in direct service activities. This service activity is related to the reading of the Al-Qur'an by Bin-Nadhor and Bil-Ghoib which also involves the community as a goal of forming a sense of Ukhuwah Islamiyah to strengthen ties of friendship and be able to grow and develop our next generation. The Qur'an is a guide to daily life. Therefore, it is not enough for us to read it until it is finished but do not understand its contents.